Targeting glioma stem‐like cell survival and chemoresistance through inhibition of lysine‐specific histone demethylase KDM2B. Issue 3 (12th February 2018) - Staberg, Mikkel; Rasmussen, Rikke Darling; Michaelsen, Signe Regner; Pedersen, Henriette; Jensen, Kamilla Ellermann; Villingshøj, Mette; Skjoth‐Rasmussen, Jane; Brennum, Jannick; Vitting‐Seerup, Kristoffer; Poulsen, Hans Skovgaard; Hamerlik, Petra
Abstract : Glioblastoma (GBM) ranks among the most lethal cancers, with current therapies offering only palliation. Inter‐ and intrapatient heterogeneity is a hallmark of GBM, with epigenetically distinct cancer stem‐like cells (CSCs) at the apex. Targeting GSCs remains a challenging task because of their unique biology, resemblance to normal neural stem/progenitor cells, and resistance to standard cytotoxic therapy. Here, we find that the chromatin regulator, JmjC domain histone H3K36me2/me1 demethylase KDM2B, is highly expressed in glioblastoma surgical specimens compared to normal brain. Targeting KDM2B function genetically or pharmacologically impaired the survival of patient‐derived primary glioblastoma cells through the induction of DNA damage and apoptosis, sensitizing them to chemotherapy. KDM2B loss decreased the GSC pool, which was potentiated by coadministration of chemotherapy. Collectively, our results demonstrate KDM2B is crucial for glioblastoma maintenance, with inhibition causing loss of GSC survival, genomic stability, and chemoresistance. Abstract : In the present report, we show that KDM2B is preferentially expressed in glioblastoma‐derived cancer stem‐like cells (GSCs) and its targeting induces DNA damage, cell cycle arrest, and apoptosis, thereby impairing maintenance of GSCs. Moreover, KDM2B inhibition sensitizes GSCs to lomustine and etoposide, both chemotherapeutics commonly used in clinical neuro‐oncology.